A Study of Reservoir Volume and Its Inundated RMs of Budhi Gandaki Hydropower Project with Respect to Dam Height Variation - Prajapati, Raghu Nath; Miya, Abdul Hai; Raut, Bhagwati; Aryal, Aayukta Raman; Shrestha, Beebas (SCITECH Nepal, 2018)
Water resources are the most important natural resources as they are renewable natural resources and also abundantly available in the context of our country. It has huge number of large rivers and streams which has got very high potential of generating hydroelectricity. Construction of any civil engineering structure is not only fully about the design on which it based on but also the impact it does to the surrounding of it. Huge civil engineering structure like Budhi Gandaki hydropower project is a proper demand for the country like ours. Budhi Gandaki Hydropower project site is west of Kathmandu having £576261 and N3079050. The project has the huge potential of generating about 1200 MW which is obtained by constructing a high rise dam height of 263m. In "A Study of Reservoir Volume and its Inundated RMs of Budhi Gandaki Hydropower Project with Respect to Dam Height Variation", the analysis was done with the help GIS to find out various inundation nature of the reservoir at dam height variation and even DEM of the Nepal was used to find the catchment area, inundation area, inundation volume and affected RMs of the project.